Discipline and Punishment in ZANLA 1964––1979 - Mazarire, Gerald C. (Taylor and Francis, 2016)
Discipline is a subject more referred to than examined in the history of Zimbabwe’s liberation war. While there are references to the administration of punishment in specific circumstances or, more often, contemptuous remarks by Rhodesian soldiers regarding the unprofessional conduct of guerrillas in general, few studies have investigated thesystematic deployment of disciplinary structures in Zimbabwe’s guerrilla movements. Drawing on internal sources, this article explores this subject by focusing on the Zimbabwe National Liberation Army (ZANLA), the armed wing of the Zimbabwe African National Union (ZANU), in the 1960s and 1970s. These sources show that there was a thin line between the party and its army. The rules governing both were mutually interchangeable under the principle that the ‘vanguard party’ should guide the gun. The orthodox view regarding the ‘triumph of the military’ in ZANU is confirmed, but the article goes further to demonstrate how the ZANU High Command gained the capacity to determine the management of discipline and the administration of punishment such that it was, in practice, the gun that guided the party. With time ZANU became highly militarised. The article identifies three phases of this process. Towards the end of the war, and after ZANU and ZANLA had undergone a series of internal crises, they faced a serious challenge of ‘anarchism’ in the operational zones. This required ZANU’s renewed Central Committee to organise a strategy to restore order. This strategy, spearheaded by the Departments of Defence and of the Commissariat, inadvertently elevated these two units as the party’s most influential and powerful organs, a legacy that haunts ZANU to this day.